The Influence of Speakers’ Voice in TOEFL Listening Test - Niza Novia; Syamsul Bahri; Nurul Inayah (Universitas Syiah Kuala, 2019)
This study is aimed to find out the influence of male and female speaker in Test of English as a foreign language (TOEFL) listening test. In order to attain the needed data in this study, the researcher designed the study under quantitative research approach focused on survey design. The researcher found that the frequency in listening to female speaker in taking Test of English as a foreign language (TOEFL) listening test was higher at the highest score than in listening to male speaker. The results of the study showed that in listening to femalefemale speaker was higher avarge score achieved by the students.However, there were not too far significant differences in both avarage score. In conclusion, students’ score showed that listening to female speaker was easier to be listened by students since the the students got the higher frequency in the highest range score and mean score.